A Content Analysis of Whistleblowing Policies of Leading European Companies - Hassink, Harold (Journal of business ethics, 2007)
Since the introduction of the U.S. Sarbanes-Oxley Act in 2002 and several other national corporate governance codes, whistleblowing policies have been implemented in a growing number of companies. Existing research indicates that this type of governance codes has a limited direct effect on ethical or whistleblowing behaviour whereas whistleblowing policies at the corporate level seem to be more effective. Therefore, evidence on the impact of (inter)national corporate governance codes on the content of corporate whistleblowing policies is important to understand their indirect impact on whistleblowing behaviour. This study analyzes the contents of whistleblowing policies, and parts of corporate codes of conduct and codes of ethics, describing such policies of 56 leading European companies. By classifying the contents in seven categories, an exploratory framework was created. General contents often identified were: applicability to all employees, a group-wide scope and an authoritative tone. The most common general violations to report were breaches of internal policies and external regulations or laws. The more specific violations most frequently mentioned were criminal offences and dangers to health and safety or the environment. Contacts to report to were the direct or indirect supervisors, a compliance officer or a confidential “hotline” facility. A confidentiality guarantee was common and anonymous reporting was often possible, though sometimes discouraged. Protection against retaliation is stated by ensuring that retaliation will not happen, prohibiting it or making it punishable. The requirement of good faith was frequently given. Finally, investigation of the report was often guaranteed. Surprisingly little information is given on the treatment of whistleblowers reporting an unfounded complaint in good faith, or reporting a violation they were involved in. The study’s findings are most relevant to companies without a whistleblowing policy or those that intend to benchmark their policies, and to pan-European standard setters.